2015
DOI: 10.1017/s1092852914000819
|View full text |Cite
|
Sign up to set email alerts
|

Using neuroimaging to evaluate and guide pharmacological and psychotherapeutic treatments for mood disorders in children

Abstract: Mood disorders are increasing in childhood, and often require multimodal and comprehensive treatment plans to address a complex array of symptoms and associated morbidities. Pharmacotherapy, in combination with psychotherapeutic interventions, is essential for treatment and stabilization. Current evidence supports the use of a number of interventions in children and adolescents diagnosed with DSM-5 mood spectrum disorders, which are associated with impairments in prefrontal-striatal-limbic networks, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 89 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…Since childhood and adolescence are periods of rapid and dynamic changes in cortical maturational processes that are sensitive to perturbations, psychotropic medications may alter typical brain development trajectories toward more favorable outcomes [67,68]. Although it is important to intervene early and prevent a first episode, not all youth at risk develop Bipolar Disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Since childhood and adolescence are periods of rapid and dynamic changes in cortical maturational processes that are sensitive to perturbations, psychotropic medications may alter typical brain development trajectories toward more favorable outcomes [67,68]. Although it is important to intervene early and prevent a first episode, not all youth at risk develop Bipolar Disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In treatment of mental problems, these disorders are targeted, and changes occurred as a result of medical treatment can be shown by using cranial imaging examinations (3)(4)(5). It was reported that similar biological changes were determined in individuals who were treated by psychotherapy method without drug treatment as the ones treated by medications (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%